Sedimentary Organic Matter and Phosphate along the Kapuas River (West Kalimantan, Indonesia) - Pei Sun Loh; Chen-Tung Arthur Chen; Gusti Z. Anshari; Jiann-Yuh Lou; Jough-Tai Wang; Shu-Lun Wang; Bing-Jye Wang (Journal of Chemistry)
This study assessed the sedimentary organic matter (OM) and phosphate along the world’s longest river on an island: the Kapuas River in West Kalimantan, Indonesia. The surface sediment was tested using the loss-on-ignition experiment to determine the % labile OM, % refractory OM, and % total OM and the Rp values (the ratio of refractory to total OM). The C/N ratios and the inorganic phosphate (IP), organic phosphate (OP), and total phosphate (TP) levels were also determined. The combination of high Rp values and low C/N ratios along the upper river indicated the possible presence of relatively degraded material; the low Rp values and high C/N ratios downstream were indicative of a fresher terrestrial signal. Sedimentary P levels were the highest along the densely populated areas downstream from the Kapuas River; the second highest along the midstream river, which is surrounded by oil palm plantations; and the lowest along the upper river, which is surrounded by forest. Higher levels of OM, IP, OP, and TP downstream along the Kapuas River indicated the presence of anthropogenic sources of OM and P.